2014
DOI: 10.1186/1471-2415-14-47
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic and ocular risk factors with neurosensory retinal detachment in diabetic macular edema: a case–control study

Abstract: BackgroundDiabetic macular edema (DME) with neurosensory retinal detachment (NSD) remains an important cause of visual loss in patients with diabetes. The aim of the study was to elucidate the association of systemic and ocular risk factors with NSD in DME.MethodsIn a retrospective case–control study, we reviewed clinical records of all the subjects with DME seen between January 2010 and December 2010. Cases and controls were selected based on optical coherence tomography and stereoscopic biomicroscopy review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…To date, the reason why subretinal fluid only appears in a small portion of diabetic macular edema has remained unclear. High glycosylated hemoglobin levels and systemic hypertension have been linked to the breakdown of blood retinal barrier that makes fluid tend to shift into the subretinal space [ 17 , 18 ]. High glucose levels increased osmotic and oxidative stress which impaired RPE pumping function as suggested in the previous study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the reason why subretinal fluid only appears in a small portion of diabetic macular edema has remained unclear. High glycosylated hemoglobin levels and systemic hypertension have been linked to the breakdown of blood retinal barrier that makes fluid tend to shift into the subretinal space [ 17 , 18 ]. High glucose levels increased osmotic and oxidative stress which impaired RPE pumping function as suggested in the previous study [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous study had much higher average HbA1c, 10.05% in SRF group, compared with 7.0% in our study. In addition to RPE dysfunction, literatures had pointed out that prolonged hyperglycemia and hypertension could directly or indirectly contribute to upregulation of vascular endothelial growth factors due to sustained ischemia and RPE injury [ 18 20 ]. One clinical research showed in 15 eyes that subretinal fluid reflectivity quantified by OCT was highly associated with increased levels of intraocular VEGF that led to the breakdown of blood retinal barrier [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta ve ark. 'nın 17 2014 yılında yayınladıkları çalışmada yüksek sistolik ve diyastolik kan basıncının DMÖ'de seröz makuler dekolman gelişimi için bağımsız ve önemli bir risk faktörü olduğu ifade edilmekte olup; yaş, diyabet süresi, açlık kan şekeri, tokluk kan şekeri, HbA1c, hemoglobin düzeyi ve hipertansiyon varlığının SMD oluşma riskini arttırmadığını ifade edilmiştir.HT'nin özellikle de malign hipertansiyonun SMD'nin iyi bilinen bir nedeni olduğunu bildiren çalışmalar da bulunmaktadır. 18 Bizim çalışmamızda seröz makuler dekolman bulunan olgularda sistemik faktörler değerlendirildiğinde HT öyküsü daha yüksek orandaydı ve bu fark istatiksel olarak da anlamlıydı.…”
Section: Discussionunclassified
“…A recent case-control study of neurosensory retinal detachment among patients with diabetic macular oedema suggested that high blood pressure could be a risk factor for retinal detachment 8. Despite its limitations—a very specific research question and a sample size of only 33 cases and 21 controls—the study introduced an interesting hypothesis linking vascular risk factors to retinal detachment.…”
Section: Introductionmentioning
confidence: 99%